ACCELERATION OF HEAT AND MATTER EXCHANGE PROCESSES IN THE FINAL DISTILLER WITH A CONVEX-CONCAVE PLATE - Ismoilov, Kozimjon; Khamdamov, Anvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article, it can be seen that the liquid-vapor system and the interfacial substance exchange and the reduction of hydraulic resistances are caused by the increase in the mutual contact of liquid and vapors using column devices. Use of modern coiled equipment in extraction plants and familiarization with their modes of operation, their application to industrial enterprises. Speeding up the exchange of substances due to the expansion of the phase surface in the final distillation process and the use of new technological equipment.